Peran UMKM Dalam Meningkatkan Perekonomian Mandiri (Studi Kasus: Pengrajin Lencana Desa Pasir Wetan) - Farkhan Syabani (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2021)
Economic activity is an activity that cannot be separated from the life of every human being. The state is the largest economic structure where the government carries out various policies to be able to run and improve the country's economy. The government also takes part in helping MSME actors advance and develop their businesses. MSMEs also have a very important role for the growth and development of the Indonesian economy. Although sometimes MSME actors experience several obstacles which include lack of knowledge and knowledge of maximizing technology that is growing. In addition, MSMEs also have a very significant role in helping to improve the country's economy. The purpose of this study was to determine the role of MSMEs in improving the independent economy (Special study: Badge craftsmen in Pasir Wetan Village), by examining badge craftsmen, where data were obtained from direct observations and interviews. The results are: Badge craftsmen who are MSMEs who will continue to innovate and be creative to create an independent economy that is able to compete with other craftsmen so that they can also increase their income and standard of living for the better.